Constitutive expression of recombinant clumping factor of Staphylococcus aureus in Escherichia coli - Ivanova, Victoria; Pozur, V. (My University, 2003)
Experiments for optimization of the clfA gene expression in E.coli BL21 (DE3)Gold cells were conducted. It has been shown the reducing of the strain efficiency and the elimination of the plasmid during the cultivation of a producer. Several methods for raising the amount of plasmid-containing cells and increasing the yield of recombinant protein were proposed. Bacterial growth medium was selected to make this process more efficient. In such conditions after IPTG induction of the recombinant cells we have got high level of a soluble protein (about 30 % of total cellular protein).
Keywords: clumping factor; expression; хлопьеобразующий фактор; экспрессия; пластівцевоутворюючий фактор; експресія; кафедра експертизи харчових продуктів